Endovascular coil embolization of a spinal epidural arteriovenous fistula with associated cord compression from an enlarging venous varix. Issue 6 (December 2015) - Ding, Dale; Starke, Robert M; Manka, David; Crowley, R Webster; Liu, Kenneth C
Spinal arteriovenous fistulas (AVFs) completely isolated to the epidural compartment are exceedingly rare. As such, the optimal management of these lesions is poorly defined. The aim of this technical note is to describe our endovascular technique for the occlusion of a purely epidural AVF of the thoracic spine associated with cord compression from an associated enlarging venous varix. A 40-year-old male presented with severe right-sided back pain and anterior thigh numbness after a sports-related back injury six months previously. Spinal magnetic resonance imaging (MRI) showed an enhancing, extradural mass lesion at T12. Spinal angiography revealed an epidural AVF supplied by a radicular branch of the right T12 subcostal artery and draining into the paravertebral lumbar veins, as well as an adjacent 20 × 13 mm 2 contrast-filling sac, compatible with a dilated venous varix. There was no evidence of intradural venous drainage. We elected to proceed with endovascular treatment of the lesion. At the time of embolization five days later, the venous varix had enlarged to 26 × 16 mm 2 . The T12 epidural AVF was completely occluded with two coils, without residual or recurrent AVF on follow-up angiography one month later. The patient made a full recovery, and complete resolution of the venous varix and cord compression were noted on MRI at three months follow-up. Endovascular coil embolization can be successfully employed for the treatment of appropriately selected spinal epidural AVFs. Cord compression from an enlarging venous varix can be treated concurrently with endovascular occlusion of an associated spinal epidural AVF.